Upper quarter Y-balance test in collegiate softball players: bilateral arm comparison and influence of reach order - Christian, K. M.; Moran, M. F. (International Journal of Athletic Therapy & Training, 2021)
The upper quarter Y-balance test is an upper extremity, closed kinetic chain assessment that requires individuals to reach in three directions while in a three-point plank position. The upper quarter Y-balance test was performed in 22 collegiate softball players (19.95 ± 1.52 years) to determine the (a) differences between throwing and nonthrowing (NT) sides and (b) influence of reach sequence. While stabilizing on the NT side, participants reached significantly further in the inferolateral direction than the throwing side (NT: 83.7 ± 12.2% arm length; throwing: 80.1 ± 10.5% arm length; p = .03; effect size = -0.57). Altering reach sequence significantly influenced medial reach (p < .01, effect size = 0.66) and composite score (p = .017, effect size = 1.03) when stabilizing on the NT side. Asymmetries in upper quarter Y-balance test in collegiate softball players should be interpreted cautiously, and an ordered test sequence should be consistently followed.